Regucalcin regulation by extracellular calcium in prostate cells - Rodrigues, Daniel Barreira (2013)
Prostate cancer is one of the most diagnosed diseases in men at the present time. It is well known that changes in calcium (Ca2+) homeostasis are derived from modifications in Ca2+ regulating elements. Regucalcin (RGN) is a Ca2+-binding protein which plays an important role in maintenance of intracellular Ca2+ homeostasis and regulation of apoptosis and proliferation. RGN is underexpressed in prostate cancer cells, suggesting that a loss of RGN expression may be associated with tumor development. In vivo studies have also shown that Ca2+ administration acts as a regulator of RGN expression in liver and kidney tissues. However, no studies on the characterization of RGN regulation by extracelular Ca2+ in prostate cells have been conducted. To attain this goal, prostate cells were stimulated with different doses of CaCl2 during several periods of time. To assess RGN mRNA and protein expression, Real Time PCR and Western Blot were carried out, respectively. Moreover, the cell viability in response to treatments was evaluated through MTS assays. Our results show that nonneoplastic PNT1A cells present higher levels of RGN when compared to neoplastic LNCaP or PC3 cells. We also verified that RGN expression in PNT1A cells is up-regulated by extracellular Ca2+ at 1,5h after stimuli, but its expression decreases after 3h of stimulation. We also showed that high doses of extracellular Ca2+ induce different effects on cell proliferation between PNT1A and LNCaP cells. This study led us to conclude that RGN appears to be regulated by extracellular Ca2+ levels in prostate cells and that an elevation of extracellular Ca2+ promotes high rates of cell proliferation in LNCaP cells, possibly due to the down-regulation in RGN expression in cancer cells.